Association Between Blood Glucose and Body Mass Index With Dietary Diversity and Physical Activity: A Cross‐Sectional Study on Marma Tribes of Bandarban in Bangladesh - Sadnan Hossain; Akibul Islam Chowdhury; Md. Nawal Sarwer; Fouzia Akter; Nasima Akter Mukta (Health Science Reports, 2025)
ABSTRACT Background The increase in overweight and obesity cannot be exclusively ascribed to environmental or lifestyle factors, since a substantial proportion of this phenomenon is impacted by genetic and racial factors. This study investigated the link between body mass index (BMI) and fasting blood glucose (FBG) levels among Marma tribal community members in Bangladesh. Methodology A cross‐sectional study was carried out on the Marma tribe of the Bandarban using random sampling techniques to select the participants. A total of 208 (74 male and 134 female) respondents participated, and a standardized questionnaire was used to collect data. In addition to descriptive statistics, χ2, and logistic regression model were employed for analysis at a 5% significance level. Result This study reveals that 65.9% of the people belong to the 30–50 age group, followed by 28.8% of the 51–70 age group associated with BMI (p < 0.024). The prevalence of obesity (46%) is higher among females (p < 0.05). Physical activity level is associated with BMI (p < 0.05). Among all the subjects, 14.9% are diabetic, 37.5% are prediabetic, and 46.7% belong to the normal blood glucose range. The relation between physical activity level and body mass index is notable (p < 0.05). Blood glucose level and dietary diversity score are also significant (p < 0.05). Conclusion There is no significant association between BMI and blood glucose levels, but a positive correlation exists. The BMI tends to be greater among females. Future research could compare it with non‐tribal groups and use the HbA1c approach for a more comprehensive evaluation.